Autonomous motivation and quality of life as predictors of physical activity in patients with schizophrenia - Costa, R (2018)
Aim: Being physically active is a complex behaviour in patients with schizophrenia. Several factors were identified as barriers to achieving active behaviours in this population. Therefore, the purpose of this study was to investigate among a number of barriers what predicts the most on physical activity (PA) in patients with schizophrenia. Methods: A total of 114 patients (28♀) with schizophrenia were included. Body mass index (BMI) was calculated. Autonomous and controlled motivation (Behavioural Regulation in Exercise Questionnaire – 3), self-esteem (Rosenberg Self-esteem scale), quality of life (World Health Organization Quality of Life Scale – Brief version) and functional exercise capacity (6-minute walk test – 6MWT) were evaluated. Multiple Regression Analysis was applied to assess the effect of these variables on Total PA per week (International Physical Activity Questionnaire – short version). Results: Autonomous motivation and domains of quality of life were positively correlated with Total PA per week. Stepwise multiple regression analyses showed that of all the candidate factors to predict PA, autonomous motivation and global domain of quality of life were found as significant predictors. Conclusion: Our findings help to understand the importance of autonomous motivation and quality of life for PA in patients with schizophrenia. Knowledge about these predictors may provide guidance to improve PA behaviour in this population.